Evaluation of a complex intervention for prisoners with common mental health problems, near to and after release: the Engager randomised controlled trial. (January 2023) - Byng, Richard; Kirkpatrick, Tim; Lennox, Charlotte; Warren, Fiona C.; Anderson, Rob; Brand, Sarah Louise; Callaghan, Lynne; Carroll, Lauren; Durcan, Graham; Gill, Laura; Goodier, Sara; Graham, Jonathan; et al.
Abstract : Background: Many male prisoners have significant mental health problems, including anxiety and depression. High proportions struggle with homelessness and substance misuse. Aims: This study aims to evaluate whether the Engager intervention improves mental health outcomes following release. Method: The design is a parallel randomised superiority trial that was conducted in the North West and South West of England (ISRCTN11707331). Men serving a prison sentence of 2 years or less were individually allocated 1:1 to either the intervention (Engager plus usual care) or usual care alone. Engager included psychological and practical support in prison, on release and for 3–5 months in the community. The primary outcome was the Clinical Outcomes in Routine Evaluation Outcome Measure (CORE-OM), 6 months after release. Primary analysis compared groups based on intention-to-treat (ITT). Results: In total, 280 men were randomised out of the 396 who were potentially eligible and agreed to participate; 105 did not meet the mental health inclusion criteria. There was no mean difference in the ITT complete case analysis between groups (92 in each arm) for change in the CORE-OM score (1.1, 95% CI –1.1 to 3.2, P = 0.325) or secondary analyses. There were no consistent clinically significant between-group differences for secondary outcomes. Full delivery was not achieved, with 77% (108/140) receiving community-based contact. Conclusions: Engager is the first trial of a collaborative care intervention adapted for prison leavers. The intervention was not shown to be effective using standard outcome measures. Further testing of different support strategies for prison with mental health problems is needed.